An exploratory study of the role of HRM and the transfer of German MNC sustainability values to Brazil. (16th April 2009) - Wehling, Claudia; Guanipa Hernandez, Andrea; Osland, Joyce; Osland, Asbjorn; Deller, Jurgen; Tanure, Betania; Neto, Antonio; Sairaj, Anu
Sustainability, defined here as the triple bottom line, is rapidly gaining importance as a societal and strategic business concern. Research on sustainability linked with Human Resource Management (HRM) is very limited. Although HR is often tasked with training and transferring values related to corporate strategy, an investigation of 10 German multinationals and their Brazilian subsidiaries found varying levels of HR involvement in the organisation of sustainability programmes or the transfer of German sustainability values to Brazilian subsidiaries. Content analysis of company reports resulted in an original model that includes five core components that characterise sustainability management in this sample: rationale, conceptual framework, direction, transfer and evaluation. Follow-up interviews with German and Brazilian executives specified the role of HRM in sustainability and the German-Brazilian transfer process. We conclude with suggestions for future research directions and a discussion of the model's practical HR implications for implementing sustainability initiatives.